Implementation of Importance Performance Analysis to Analyze Customer Satisfaction in PT. Bank Tabungan Negara KCP Simalingkar Medan - Lingga, Nia Astria; Sembiring, Pasukat (Journal of Mathematics Technology and Education, 2021)
The method Importance Performance Analysis (IPA) aims to measure the relationship between consumer perceptions and priorities for improving the quality of services/products which is also known as quadrant analysis. In improving the quality of service to give satisfaction to the consumer the State Savings Bank Branch Office (KCP) Simalingkar Terrain require businesses to meet the expectations of customers, so that customers gain satisfaction with the services provided State Savings Bank KCP Simalingkar Medan. To find out how the level of customer satisfaction with service quality at the State Savings Bank KCP Simalingkar Medan, customer satisfaction was measured using the method Importance Performance Analysis (IPA). There are 25 valid attributes that are asked to customers who use the services of the State Savings Bank. The value of the highest level of service quality compliance is 98.53%, namely the security and confidentiality of customer data. The suitability value from the results of the comparison between performance and interest obtained an average value of 95.70% so that it can be concluded as a whole that the attribute is included in the appropriate category if the value of the level of conformity is close to 100% and is above the average, it can be said that the level of quality conformity The services of the State Savings Bank of KCP Simalingkar Medan are good.